Communicative language teaching. an introduction - Littlewood, William (Cambridge : New York : Melbourne : Cambridge University Press, 2008)
An introduction to communicative language teaching for practising classroom teachers.
Includes bibliography and index.
Keywords: Language and languages -- Study and teaching; Communicative competence; Languages, Modern -- Teaching -- Foreigners